Primary pulmonary classic Hodgkin’s lymphoma - Binesh, Fariba (BMJ Publishing Group, 2011)
Primary pulmonary Hodgkin’s lymphoma (HL) is very uncommon. The diagnosis is only made if nodal involvement is absent and disease elsewhere has been excluded. Here, the authors present a 54-year-old female with fever, chills, sweating, non-productive cough, anorexia and weight loss. Chest x-ray and CT scan revealed bilateral and multiple nodules especially in upper pulmonary lobes without mediastinal lymphadenopathy. The biopsy from lung nodule revealed classic HL which was primary.